State-Level Disparity in Lung Cancer Survival in the United States - Lee, Yu-Che; Calderon-Candelario, Rafael A.; Holt, Gregory E.; Campos, Michael A.; Mirsaeidi, Mehdi (Frontiers in Oncology, 2020)
Rationale: The cancer mortality-to-incidence ratio (MIR) can serve as a population-based indicator for cancer care outcomes. In the US, evaluation of lung cancer survival by individual states has not been evaluated. Objective: To assess the association between lung cancer survival by using MIRs and state-level health disparities in the United States. Methods: We calculated 5-year lung cancer MIR averages from 2011 to 2015 using the United States Cancer Statistics (USCS) data. America's Health Rankings (AHR) is a platform using weighted measures in five different categories to calculate annual state health rankings. Five-year averages from 2011 to 2015 of the health uninsured rate and 4-year averages from 2011 to 2014 of health spending per capita were obtained from the U.S. Census Bureau and Centers for Medicare & Medicaid Services. Linear regression analyses were performed to determine the associations between cancer survival value (CSV) = (1 – MIR) × 100% and state health variables. Results: During the study period, the 5-year averages of age-adjusted incidence, mortality rates, and CSVs were 60.3 ± 2.1 per 100,000 population, 43.4 ± 2.1 per 100,000, and 27.9 ± 3.9%, respectively. Among the 50 states, Connecticut had the highest CSV (38.6 ± 1.7%) whereas Nevada had the lowest CSV (18.7 ± 6.5%). Hawaii had the highest health ranking and Mississippi had the lowest ranking in 2016. States with better health rankings, lower health uninsured rates, and higher health spending were significantly associated with higher CSVs (R2 = 0.418, P < 0.001; R2 = 0.352, P < 0.001; R2 = 0.142, P = 0.007, respectively). Conclusions: There are significant differences in lung cancer survival within the United States. Lung cancer survival by using CSV was strongly associated with state health disparities, and it can be an applicable measure to evaluate the state-level health disparities in the United States.